2001
DOI: 10.3136/fstr.7.239
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Glucosides are Hydrolyzed to Quercetin in Human Oral Cavity to Participate in Peroxidase-Dependent Scavenging of Hydrogen Peroxide.

Abstract: It has been reported that consuming food which contains flavonols is related to the decrease in risks to arteriosclerosis and cancer. One objective of this study was to elucidate the metabolism of quercetin and the glucosides (quercetin 3,4¢-diglucoside and quercetin 4¢-glucoside) present in onion soup, in the oral cavity. Not only quercetin glucosides but also quercetin were found in whole saliva which was collected 15 min after eating onion soup. Quercetin seemed to be formed by deglucosidation of the glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…5). The inhibition may be due to competition between thiocyanate and quercetin for compound I of salivary peroxidase, which is formed by direct reaction between H 2 O 2 and peroxidase, as discussed previously (Hirota et al, 2001). The inhibition of quercetin oxidation by thiocyanate also suggests that the oxidation product of thiocyanate, hypothiocyanate, does not rapidly oxidize quercetin at pH 7.6.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…5). The inhibition may be due to competition between thiocyanate and quercetin for compound I of salivary peroxidase, which is formed by direct reaction between H 2 O 2 and peroxidase, as discussed previously (Hirota et al, 2001). The inhibition of quercetin oxidation by thiocyanate also suggests that the oxidation product of thiocyanate, hypothiocyanate, does not rapidly oxidize quercetin at pH 7.6.…”
Section: Discussionmentioning
confidence: 75%
“…Since polyphenols are normally ingested by mouth as vegetables and fruits, elucidation of their metabolism in the oral cavity is also important. In previous papers, we reported that when onion soup, which contains quercetin glucosides (Hirota et al, 1998(Hirota et al, , 1999, is ingested, the glucosides are hydrolyzed to the aglycone quercetin, and that quercetin is degraded in the oral cavity (Hirota et al, 2001). The degradation is also observed when quercetin is added to collected saliva with and without externally added H 2 O 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the concentrations of nitrite and HPA tend to be higher in individuals with age of 60-year-old or more. Quercetin (30 µM) suppressed nitrite-induced O 2 NHPA formation more than 90% in bacterial fraction at pH 5 and quercetin can stay in the oral cavity for several hours after ingestion of onion soup (Hirota et al, 2001). Chlorogenic acid, which can also scavenge NO 2 , stays in the oral cavity for several hours after ingestion of coffee (Takahama et al, 2007b).…”
Section: Nitrationmentioning
confidence: 99%
“…Among these components, antioxidative polyphenols may be important from the standpoint of health in the oral cavity. It has been reported that quercetin and the glucosides are present in the saliva after ingestion of onion soup, and that the flavonols remained in the oral cavity for several hours after the ingestion (Hirota et al, 2001). The importance of the phenolics as antioxidants in the oral cavity is deduced from the report that polyphenols can scavenge reactive oxygen species generated by SPMN (Hirota et al, 2002).…”
mentioning
confidence: 99%